Up-Regulation of TLR-4 in the Brain After Ischemic Kidney-Induced Encephalopathy in the Rat - Salama, Mohamed; Mohamed Farrag, Sally; abulfath abulasrar, Sarah; Mohamed Amin, Maha; Abdel-Aziz Ali, Azza; Sheashaa, Hussein; Sobh, Mohamed; Arias-Carrion, Oscar (CNS & Neurological Disorders - Drug Targets, 2013)
Ischemic acute kidney injury (AKI) is usually accompanied by neuroinflammation-induced encephalopathy. However, the specific mechanism remains unclear. Toll-like receptors (TLR), specifically TLR-4 has been linked to ischemic reperfusion injury in different organs like kidney, brain and liver. Here, we induced an ischemic reperfusion kidney injury in Sprague Dawley rats. All animals were evaluated using behavioral tests which revealed locomotor activity and motor disturbances in the AKI group. The brains were then examined by immunostaining with ionized calcium binding adaptor molecule 1 (microglial marker) and TLR-4 antibodies. The histological analysis revealed significant up-regulation of TLR-4 in the hippocampus and striatum in the AKI group. These data demonstrate for the first time, the triggering effect of TLR-4 on AKI-induced neuroinflammation in the brain that may lead to AKI-induced encephalopathy. This would also generate a novel hypothesis that using TLR blockers may have a role in preventing AKI effects on the brain.
Keywords: neuroinflammation